2015
DOI: 10.1080/10548408.2015.1051642
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Quality Antecedents and Moderating Effects of Experiential Value in a Mega-Event

Abstract: This study aims to explore (1) the underlying dimensions of experiential value (EV),(2) the quality antecedents of EV, and (3) the moderating effects of EV on the relationships between the quality dimensions of Expo 2012, Yeosu, Korea, and visitor satisfaction. Although gaining event experience is a crucial reason why event visitors attend certain events, EV has yet to be fully investigated in event literature. This study offers an expanded view of the event consumption experience from the EV perspective, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…A total of 52 items were initially generated. The potential attributes of honeymoon tourism were derived from the existing destination and honeymoon tourism literature, along with the following domains: accessibility (Cong, 2016; Lee et al, 2010; Vassiliadis, 2008; Wu et al, 2018), attraction (Buhalis, 2000; Bulcroft et al, 1999; Kim & Agrusa, 2005; Kozak, 2001), destination environment (Bulcroft et al, 2000; Fernandes & Cruz, 2016; Jang et al, 2007; Kim & Agrusa, 2005; Lee et al, 2010), destination image (Beerli & Martin, 2004; Kim & Agrusa, 2005; Lee et al, 2010), hospitality of local residents (Cong, 2016; Kim, Holland, & Han, 2013; Tosun et al, 2015; Žabkar et al, 2010), honeymoon service providers (Albacete-Saez et al, 2007; Kim & Agrusa, 2005; Lee & Min, 2016; Wu & Li, 2017), honeymoon accommodation (Albacete-Saez et al, 2007; Anderson, 2016; Bulcroft et al, 1999; Johnson, 2010; Lee et al, 2010), dining experience (Anderson, 2016; Bulcroft et al, 1999; Kim & Agrusa, 2005; Kuoni, 2013; Lee & Min, 2016; Penner, 2009), local tour products (Anderson, 2016; Bulcroft et al, 1999; Kim & Agrusa, 2005; The Knot, 2011; Kuoni, 2013; Lee et al, 2010), and honeymooners’ privileges (Anderson, 2016; Bulcroft et al, 1997; Kim & Agrusa, 2005; Lee et al, 2010; Penner, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 52 items were initially generated. The potential attributes of honeymoon tourism were derived from the existing destination and honeymoon tourism literature, along with the following domains: accessibility (Cong, 2016; Lee et al, 2010; Vassiliadis, 2008; Wu et al, 2018), attraction (Buhalis, 2000; Bulcroft et al, 1999; Kim & Agrusa, 2005; Kozak, 2001), destination environment (Bulcroft et al, 2000; Fernandes & Cruz, 2016; Jang et al, 2007; Kim & Agrusa, 2005; Lee et al, 2010), destination image (Beerli & Martin, 2004; Kim & Agrusa, 2005; Lee et al, 2010), hospitality of local residents (Cong, 2016; Kim, Holland, & Han, 2013; Tosun et al, 2015; Žabkar et al, 2010), honeymoon service providers (Albacete-Saez et al, 2007; Kim & Agrusa, 2005; Lee & Min, 2016; Wu & Li, 2017), honeymoon accommodation (Albacete-Saez et al, 2007; Anderson, 2016; Bulcroft et al, 1999; Johnson, 2010; Lee et al, 2010), dining experience (Anderson, 2016; Bulcroft et al, 1999; Kim & Agrusa, 2005; Kuoni, 2013; Lee & Min, 2016; Penner, 2009), local tour products (Anderson, 2016; Bulcroft et al, 1999; Kim & Agrusa, 2005; The Knot, 2011; Kuoni, 2013; Lee et al, 2010), and honeymooners’ privileges (Anderson, 2016; Bulcroft et al, 1997; Kim & Agrusa, 2005; Lee et al, 2010; Penner, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The first and second sections were designed to measure PCCI/NCCI (five items each), experiential value (eight items), sense of community (eight items), and OCS (four items). All measurement items were adapted and modified to fit the study setting based on previous works (Allen, O’Toole, Harris, & McDonnell, 2010; Grzeskowiak et al, 2003; Ko & Stewart, 2002; J.-S. Lee & Min, 2016; Mathwick et al, 2001; Peterson, Speer, & McMillan, 2008). The 10 items for PCCI/NCCI were adapted from previous studies to measure economic, social, cultural, personal/community, and environmental benefits and costs.…”
Section: Methodsmentioning
confidence: 99%
“…Exhibition experiential value is influenced by many factors. For example, Lee and Min [16] found that the quality of the exhibition itself (e.g., exhibit program, admission experience, site environment) has a direct impact on the exhibition experiential value. However, research on the impact factors of exhibition experiential value remains relatively scarce, which calls for further investigation.…”
Section: Ccp Experiential Value and Exhibition Experiential Valuementioning
confidence: 99%
“…Moreover, the study addresses the second gap, concerning which exhibition-related factors have an impact on the experiential value of the exhibition in CCPs. In the existing literature, the current discussion on exhibitions is mainly related to major trade exhibitions, exhibitions in museums, or specific art exhibitions held in art galleries [12][13][14]; most studies are conducted from the participants' perspective in an attempt to explore the behavior of participants in exhibitions, the impact factors of the exhibitions, and the relationship between exhibition experiential value and satisfaction [12,[14][15][16], but few studies have examined the factors that influence the visitors' exhibition experiential value held in CCPs. Nevertheless, past research might be able to provide some clues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation